Strategic process of R & D in product development - Phua, Lucky. (2008)
In this dissertation, the changes in the emphasis on R&D as part of the economic strategy that the Singapore government had implemented to achieve the high economic growth in Singapore for the past three decades (1965 - 1998) was examined. The integrated relationship between manufacturing and R&D is illustrated to stress the importance of manufacturing to maintain high employment. This also creates the social stability to foster domestic capability and attract foreign talent who will contribute to the effectiveness of R&D and attract more investment in manufacturing.